ANALISIS SEKTOR UNGGULAN PEREKONOMIAN KOTA PONTIANAK - B01106100, HERRY ADINUGRAHA (Jurnal Pembangunan dan Pemerataan, 2013)
The research entitled The Analysis of Economic Leading Sector in Pontianak. The purposes of this research are to know and to analyze leading sectors in Pontianak which became the economic base of the sector and determine the typology of the economy leading sectors in Pontianak based on growth and contributions. The method of this research is descriptive method. The technique of data collecting used in this research is secondary data in time series namely gross regional domestic product data in Pontianak and West Kalimantan province in 2006 until 2011. The technique od data collecting used in this research is the base model economy is reflected in the analysis of Location Quotient (LQ) are equipped with typology Klassen Analysis that useful to know the leading sector in Pontianak. Based on the results of research using yhe Location Quotient method, sector have LQ greater than one and an economic base sector are electricity, gas and water, construction, trade, hotel and retaurants, transport dan communications, and the financial sector, leasing and business service as well as services sector. The sixth sector is a liading sector and drives the economic in Pontianak. The result of analysis Typology Klassen method using two components that are growth and contribution, sector that have high growth and high contribution is the construction sector, the trade, hotels and retaurants and transport and communications sector. Sector that provide low growth and low contributions were mining and quarrying and manufacturing sectors.